Business fixed investment and credit market frictions: A VECM approach for Hungary - Marianna Endrész (Magyar Nemzeti Bank, 2011)
The aim of this paper is to model the interaction between the loan market and real activity, while financial frictions are explicitly taken into account. The econometric methodology used is VECM. Johansen's approach is employed to allow for multiple cointegration. Financial frictions are captured by including balance sheet indicators of firms and banks (cash flow and the VIX index) which move the loan supply curve. For the non-financial corporate sector 3 long-run equilibrium relationships were found, each corresponding to a reduced form investment, a loan demand and a loan supply equation, where loan supply is determined by the cost of borrowing, and the cash flow of firms or the VIX index. In contrast, for manufacturing no evidence was found concerning the significance of financial frictions. Impulse response analysis is used to calculate the real effects of a loan supply shock. Various tax measures and the introduction of inflation targeting were found to have significant impact on investment.
Keywords: E22; E44; E51; C32; 330; aggregate investment; financial frictions; cointegration; error correction models